Pengukuran Kinerja Perusahaan dengan Metode Balanced Scorecard - Prasetiyatno -; Rachmad Hidayat; Issa Dyah Utami (Industrial Engineering Study Program, Faculty of Engineering, Universitas Sebelas Maret, 2011)
This research is intended to measure and analyze the company’s capability by four perspective Balanced Scorecard, identification and measure achievement of Critical Succes Factor in every perspective. This research is also using Analythical Hierarchy Process (AHP) to determine behalf wight every refuses fathom and aught perspective. The result of measurement shows that capabilility on year 2008 fiancial perspective: 3.162, customer perspective: 0.697, internal business process perspective: 0.696, lerarning ang growing perspective: 0.323. and on year 2009 fiancial perspective: 3.162, customer perspective: 0.697, internal business process perspective: 0.696, lerarning ang growing perspective: 0.323 is always consistent and stable and gets score 4.877 it means the capability is good.